Rancangan Peralihan Disposal Area dan Drainase Di Pit 2AA PT Sentosa Laju Sejahtera Site CV Anggaraksa Adisarana Loa Janan - Arda Bara Ariadi (Fakultas Teknik, 2025)
PT Sentosa Laju Sejahtera faced limitations in in-pit disposal capacity due to landslides, as well as operational disruptions caused by unmanaged rainwater runoff. This study was conducted to design an alternative disposal area and a new drainage system at Pit 2AA, located within the IUP area of CV Anggaraksa Adisarana in East Kalimantan. The methods used include rainfall analysis using the Gumbel distribution based on annual maximum rainfall data from 2014 to 2023, runoff calculation using the Rational Method, and slope stability analysis using the Janbu Simplified Method. The open drainage channels, Paritan A and Paritan B, are designed to handle a peak runoff discharge of 7.8 m³/s, with respective capacities of 9.59 m³/s and 7.92 m³/s. The proposed disposal area covers 7.62 hectares and utilizes a three-tier finger dump method from elevations 93 to 105 meters, with a total capacity of 441,310 BCM. Slope stability analysis yielded Factor of Safety (FoS) values ranging from 1.315 to 2.404, exceeding the minimum requirement of FoS ≥ 1.3 in accordance with Ministerial Decree ESDM No. 1827 K/30/MEM/2018. Therefore, the disposal and drainage designs are considered safe and technically feasible for implementation
Entry oleh Arif 2026 Maret 26
Keywords: Disposal; Drainage; Factor of Safety